68Ga-Pentixafor PET/CT in Primary Aldosteronism: Preliminary Analysis on CECT Concordance and PET/CT Avidity Patterns - Ban, Anuj; Lila, Anurag Ranjan; Karlekar, Manjiri; Barnabas, Rohit; Memon, Saba Samad; Sarathi, Vijaya; Malhotra, Gaurav; Rathod, Krantikumar; Rege, Sameer; Badhe, Padma; Harinarayan, C.V.; Bandgar, Tushar (Hormone and Metabolic Research)
68Ga-Pentixafor positron emission tomography/computed tomography (PET/CT) has shown potential in primary aldosteronism (PA) subtyping, but analysis of its diagnostic accuracy based on contrast-enhanced CT (CECT) concordance and PET/CT avidity patterns is lacking. The objective of this study was to evaluate the diagnostic accuracy of 68Ga-Pentixafor PET/CT for subtyping PA, and to assess its performance based on concordance with CECT and PET/CT avidity patterns. Clinical, biochemical, radiological, functional imaging, treatment, histopathological and follow-up details of 30 patients with PA who underwent PET/CT over two years at a tertiary centre in India were retrospectively analysed. Diagnostic accuracy of PET/CT for PA subtyping was evaluated in the whole cohort and in subgroups based on CECT-PET/CT concordance and PET/CT avidity patterns. Out of the 30 patients, final subtype classification was achieved in 15 (9 unilateral and 6 bilateral) based on surgical outcomes and/or AVS. PET/CT correctly subtyped 14/15 (93.3%) patients. CECT and PET/CT concordance was seen in 10 patients and PET/CT accuracy was 100% (10/10) in this subgroup. CECT and PET/CT discordance (CECT bilateral and PET/CT unilateral) was seen in 5 patients and PET/CT accuracy in this subgroup was 80% (4/5). PET/CT avidity patterns in the 15 patients having final subtype classification were unilateral avid(n=10), bilateral avid(n=2), and bilateral non-avid(n=3). Diagnostic accuracy of PET/CT was 90% (9/10) in patients with unilateral avidity, and 100% in those with bilateral avidity or non-avidity. Preliminary analysis of CECT-PET/CT scan concordance and PET/CT avidity patterns suggests that PET/CT demonstrates higher accuracy in certain subgroups, potentially guiding the triage for AVS.